Meningkatkan Hasil Belajar Ipa Pada Materi Gaya Dan Magnet Melalui Metode Eksperimen Siswa Kelas Vi C Sdn 6 Kendari - Uddin Uddin (Jurnal Sultra Elementary School, 2020)
The aim of this research was to improve students’ learning outcomes in Natural Sciences on the topic of magnetic force through the application of the experimental method among grade VI.C students at State Elementary School 6 Kendari. This study employed a Classroom Action Research (CAR) design, characterized by specific actions intended to enhance the learning process in the classroom. The subjects of this research were all 26 students of class VI.C, consisting of 11 boys and 15 girls. The data collected included quantitative data obtained from learning outcome tests and qualitative data obtained through observation sheets. Data collection techniques involved observing the learning process during the implementation of the experimental method and conducting learning outcome tests to measure improvement. The results of the study indicated that the use of the experimental method effectively improved students’ learning activities and learning outcomes in Natural Sciences, particularly on the topic of magnetic force.